IMPACT OF EMPIRICAL PATH LOSS MODELS ON SPATIAL TV WHITE SPACE UTILIZATION - Faruk, Nasir; A. Ayeni, Adeseko; Adediran, Yinusa. A. (European Scientific Journal, ESJ, 2014)
Regulatory bodies have called for alternative spectrum management models and techniques that would allow efficient utilization of the TV white space since the proposed cognitive radio technique may not be realized in the nearest future. For effective utilization of the spatial TV white space, and coexistence between the primary and secondary users, a reliable prediction technique is required to accurately estimate the service contours of the primary users. In this article, we present the effects of empirical path loss propagation models in predicting the TV service contour using optimized model which is based on measurements of path loss in the study area and other conventional models such as the ITU-R, COST 231, HATA, Egli and CCIR models. Results of simulations show that measured path loss models’ prediction deviates significantly from the other models that provide large protection zone around the primary cell and, thus reduce the spatial utilization of the spectrum. It was also found that the -114 dBm FCC rule for empty white space is highly conservative and significantly affects the availability of the white space.